EVALUASI EYE TRACKING TERHADAP PERSEPSI WARNA DAN GAMBAR PADA PRIMARY DISPLAY PANEL KEMASAN - Wirania Swasty; Arry Mustikawan; Moh. Isa Pramana Koesoemadinata (Fakultas Seni Rupa dan Desain ITB, 2021)
Home industry food packaging displayed on shelves in stores will compete with products from other brands that are placed close together. In order to attract consumers’ attention and assist them in the purchasing decision-making process, packaging that has a competitive advantage is needed. This research is limited to the Primary Display Panel (PDP) packaging of home industry banana chips. In previous studies, the research used was quantitative, but this does not reveal the whole story. The data recording process can support “what” the participant looks at but does not reveal “why” they look at it. For this reason, this research is aimed to establish a broader understanding of what participants perceive of the packaging design seen using eye tracking methods and why it happened. This study uses qualitative approach. The study consists of three phases: literature study, eye tracking data recording, and data processing and interviews analyzed using content analysis. The result is colors and images are perceived to be the same by teenagers and young adults. There is no connection between likes and dislikes for colors/images with colors preference in choosing snack products. The results can be used by producers and packaging designers to create packages that generate consumer purchase interest.